Women and Intellectual Life in New South Wales - 1835-1868 Ann Rusden - BYRNE, Paula Jane (Australasian Journal of Victorian Studies, 2022)
Ann Rusden arrived in the colony of New South Wales in 1834 and was to form part of society on the Hunter River near Newcastle. Her letters allow mapping of her intellectual life in theology, science and politics, and indicate widespread discussion among the women of the valley, separate from men. In Ann’s letters we have access to a colonising mindset where God was unfathomable in his actions, science and literature opened up possibilities, and women’s opinions mattered.